Experimental Examination of Nigerian Stakeholders' Views on Electricity Pricing Process - Rotimi, Mathew E.; Kutu, Augustine A.; Doorasamy, Mishelle; Moh'd, Rabiu Isah; Kolawole, Isiaka O.; Babatunde, David (Journal of Posthumanism, 2025)
Sustainable electricity pricing is still a key issue, particularly in developing economies such as Nigeria, where affordability, accessibility, and reliability of supply are vital to socioeconomic progress. This research explores stakeholder perceptions of the Multi-Year Tariff Order (MYTO) pricing regime, specifically its effectiveness in enhancing sustainable electricity provision. It evaluates the impact of electricity pricing acceptability, accessibility, and availability on consumer satisfaction and stakeholders' perceived sustainability of the MYTO model. A cross-sectional survey design was used and data were gathered from 93 electricity stakeholders, including residential consumers, with a structured questionnaire containing Likert-scale items. Multiple linear regression analysis carried out using SPSS showed that all three factors-acceptability, accessibility, and availability have a positive and significant effect on consumer satisfaction (p < 0.001). Among the three, accessibility exhibited the highest predictive power (β =0 .640), followed by availability (β = 0.467), and then acceptability (β = 0.368). The model accounted for 42.0% of the variation in stakeholder satisfaction (R² = 0.420), demonstrating a significant impact of service quality facets on public opinion. These results confirm that sustainable electricity pricing should be grounded not just on cost recovery mechanisms but also on pricing transparency, ease of access, and reliability of supply. The research provides appropriate policy implications for energy reform in Nigeria and comparable developing contexts, calling for more inclusive, transparent, and infrastructure-sensitive pricing strategies in order to engender public confidence and ensure long-term sustainability in the electricity industry